Parathyroid hormone - a bone anabolic and catabolic agent. - Poole, K; Reeve, J (2005)
A key factor in the control of bone remodelling is parathyroid hormone (PTH), the principal regulator of calcium homeostasis. Elevated levels of PTH increase bone turnover, leading to either anabolic or catabolic effects on the skeleton depending upon the pattern and duration of elevation. New evidence indicating that downregulation of an osteocyte signal (sclerostin, the SOST gene product) occurs in response to intermittent PTH has rekindled interest in the key role played by osteocytes and bone-lining cells in co-ordinating surface anabolic activity. Microarray analysis has also delineated many genes and pathways regulated by intermittent and continuous PTH in osteoblasts and whole bones.